Inhibition of D-Ala:D-Ala ligase through a phosphorylated form of the antibiotic D-cycloserine. Issue 1 (December 2017) - Batson, Sarah; de Chiara, Cesira; Majce, Vita; Lloyd, Adrian; Gobec, Stanislav; Rea, Dean; Fülöp, Vilmos; Thoroughgood, Christopher; Simmons, Katie; Dowson, Christopher; Fishwick, Colin; de Carvalho, Luiz; et al.
Abstract D-cycloserine is an antibiotic which targets sequential bacterial cell wall peptidoglycan biosynthesis enzymes: alanine racemase and D-alanine:D-alanine ligase. By a combination of structural, chemical and mechanistic studies here we show that the inhibition of D-alanine:D-alanine ligase by the antibiotic D-cycloserine proceeds via a distinct phosphorylated form of the drug. This mechanistic insight reveals a bimodal mechanism of action for a single antibiotic on different enzyme targets and has significance for the design of future inhibitor molecules based on this chemical structure. The antibiotic D-cycloserine (DCS) targets the peptidoglycan biosynthesis enzyme D-Ala-D-Ala ligase (Ddl). Here the authors reveal the DCS inhibitory mechanism by determining the structure ofE. coli DdlB with a phosphorylated DCS molecule in the active site that formed in crystallo and mimics the D-alanyl phosphate intermediate.